Histoire de la réception et histoire du livre - Roger Chartier (Sillages Critiques)
This article opens with a critical examination of the notions of ‘reception’ and ‘book history’. It scrutinizes the relevance of the notions of “horizon of expectation” and “interpretive community” proposed by Jauss and Fish, and also underlines their limits, since these approaches consider texts only in their linguistic dimension and tend to erase the social determinations of reading. The analysis then highlights the importance of developments within the field of book history, which branched out into the history of graphic culture with Petrucci and into the sociology of texts with McKenzie. In each case, the very materiality of the text, the form of its inscription and publication, are considered crucial to its mode of reception. For its demonstration the article develops two case studies devoted to seventeenth- and eighteenth-century England, which closely associate the materiality of texts with the signification of the works: firstly, the different modes of circulation of Shakespeare’s plays and poems (in quarto or folio formats, in collections linking them with other works and other authors, in commonplace books or as quotations in eighteenth-century Shakespearean “Beauties”), and secondly, the multiple forms of appropriation of Don Quixote in England: translations, theatrical adaptations, abridged editions. The conclusion of the article summarises the textual clues or ‘non-verbal’ elements that propose or impose expectations, interpretations and receptions of the works.